Effect of Mobile Banking on the Banking Behaviour of Informal Sector Workers in Accra, Ghana - Azumah, Shaibu Baanni; Balinto, Christopher; Adzawla, William; Osei-Baafi, Linda Akoto (Journal of Asian Business Strategy, 2020)
Improving financial inclusion of informal sector workers is a major concern for economic development. The emergence of mobile banking and its increasing acceptability and use do present an opportunity to improve banking behaviour among informal sector workers. This study estimates the effect of mobile banking service on the banking behaviour of informal sector workers in Accra, Ghana. A probit regression model was fitted to a survey data of 296 respondents. The result indicates that although the introduction of mobile banking service has a positive effect on mobile banking, less than half of the respondents have changed their banking behaviour as a result of the introduction of mobile banking service. The respondents also perceived that the introduction of mobile money service has not led to a significant change in ineffective saving methods. Other factors that significantly influenced the banking behaviour were sex, age and income of the respondents. It is concluded therefore that, mobile banking service can improve financial inclusion among informal sector workers. However, an effective remedy should be established to address the emerging risks associated with the use of mobile banking service and to improve its security features.